UPAYA PELESTARIAN TARI SI KAMBANG MANIH DALAM MASYARAKAT DI KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Idol Fatria; Desfiarni Desfiarni; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2015)
Abstract This article was written for describing the efforts done to preserve Si Kambang Manih dance. This preservation was focused on the learning process or accustoming the young generation to their cultuture. This was a qualitative research which used experimental method. The data was collected through interview, observation, and documentation. The instrument of the research was the researcher herself. The data gotten was analyzed by using Miles and Huberman model. It then was selected, reduced, presented and verivied. The result of research indicated that the efforts done preserve Si Kambang Manih dance was by giving information about the dance and indroducing it to people in Kecamatan Batang Kapas Kabupaten Pesisir Selatan. These were done by teaching the dance to the society. The activity was carried out by the researcher assisted with Tuo Tari. Keyword: Effort, preserve, dance Si Kambang, and Manih